Germanium-doped Metallic Ohmic Contacts in Black Phosphorus Field-Effect Transistors with Ultra-low Contact Resistance. Issue 1 (December 2017) - Chang, Hsun-Ming; Charnas, Adam; Lin, Yu-Ming; Ye, Peide; Wu, Chih-I; Wu, Chao-Hsin
Abstract In this work, we demonstrate for the first time an ultra-low contact resistance few-layered black phosphorus (BP) transistor with metallic PGex contacts formed by rapid thermal annealing (RTA). The on-state current of the transistor can be significantly improved and the ION /IOFF ratio increases by almost 2 order. The hole mobility is enhanced by 25 times to 227 cm2 V−1 s−1 . The contact resistance extracted by the transfer length method is 0.365 kΩ∙μm, which is the lowest value in black phosphorus transistors without degradation of ION /IOFF ratio. In addition, the I-V curve of the transistor with PGex contact is linear compared to that with Ti contact at 80 K, indicating that a metallic ohmic contact is successfully formed. Finally, X-ray photoelectron spectroscopy is used to characterize the PGex compound. A signal of P-Ge bond is first observed, further verifying the doping of Ge into BP and the formation of the PGex alloy.